The role of local and global preparation in the embodiment of the literary genre’s interference phenomenon in Kurdish novels - . Hayder Jawhar Ahmed; Pakhshan Sabr Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Literary genre interference is an important subject to be written about in literary criticism. Throughout this study, the role of local and global preparation in the embodiment of the literary genres interference phenomenon in Kurdish novels has been discussed in detail. Within this study, we refer to local preparation especially the role of the uprising of Kurdish people in 1991 and its impact on literary genre interference. Also, the effect of mass media on novels has been analyzed. The impact of technology and science development, new liberalism, multinational companies, and free markets have shown as part of the global preparation role of literary genre interference which really they have a great impact on the new style of Kurdish novels. In the practical part of this study, some examples of Kurdish novels have been concentrated on; throughout them, the reality of the effects has been proven.